Pengaruh Tipe Kepribadian Big Five Personality dan Self-compasion terhadap Loneliness pada Remaja dengan Orang Tua Bercerai - Irma Rosalida Lubis; Mauna Mauna; Ernita Zakiah; Deni Krisnaputra; Chandra Putri Hafidia Sukmana (Jurnal Online Psikogenesis, 2021)
This study aims to determine the effect of the big five personality and self-compassion towards loneliness in adolescents with devorced parents. This research uses quantitative methods.The measuring instrument used to measure loneliness is De Jong Gierveld Loneliness Scale (DJGLS). The big five personality is measured by Big Five Inventory (BFI) and the measuring instrument used to measure self-compassion is Self-Compassion scale by Neff. Data was processed using reggresion analyze with three predictor. The main result of this research there is significant effect of Big Five Personality on loneliness in adolescents with divorced parents, the percent of significant effect a following by dimension OCEAN is 5,2%, 3,1%, 18,6%, 7% and 26,1% and the is an effect of self-compassion on loneliness in adolescents with divorced parents, there is percent 5,7% that the resulting effect is negative which indicates that the higher the self-compassion, the lower the loneliness.